Cost-effectiveness analysis of antiemetics therapy in breast cancer patients with moderate emetogenic chemotherapy in Prof. Dr. Margono Soekarjo Hospital, Indonesia - Ida Dzikriyani; Didik Setiawan (Pharmaciana, 2021)
Chemotherapy-induced nausea and vomiting (CINV) significantly reduce the life quality of cancer patients. A 5-HT3 receptor antagonist, corticosteroid, and H2-blocker have been used to control moderate nausea and vomit in cancer patients. The exploration of the cost-effectiveness of several antiemetic combinations in breast cancer patients in Prof. Dr. Margono Soekardjo Hospital, Purwokerto, Indonesia was the aim of this research. Seventy-four Breast cancer patients who have prescribed moderate-emetogenic chemotherapy during the year 2017-1019 were included in this research. There were fifteen patients treated with the combination of ondansetron and dexamethasone (OD). Fourteen patients were treated with the combination of ondansetron and ranitidine (OR). Thirty-five patients were treated using ondansetron, dexamethasone, and ranitidine (ODR) combination. The effectiveness was represented by the absence of acute nausea and vomiting after receiving chemotherapy. The ODR combinations showed the highest effectivity on diminishing nausea and vomiting among breast cancer patients (0.400), followed by the OD combination (0.267) and the OR combination (0.214). However, the ODR combination generates the highest cost (4.6 million rupiahs) compared to other antiemetics combinations. Compared to the combination of ondansetron and dexamethasone, the combination of ODR provides higher ICER (ICER of 13 Million Rupiahs per case prevented) than the combination of OR (ICER of 8.5 million Rupiahs per case prevented). In conclusion, the combination of ondansetron, dexamethasone, and ranitidine generates the highest cost. It also provides the highest effectiveness in preventing nausea and vomiting.